1064 THINK STOOL CHART. (14th June 2022) - Crawford, J; Khanum, T; Lau, E; McNamee, M
Abstract: Introduction: Bowel care is an important part of care for older people. This quality improvement project (QIP) was carried out on the Older Person's Assessment Unit at Arrowe Park Hospital which is a 24 bed acute frailty unit. Locally we found inadequate documentation of stool charts. This had the potential to cause problems related to constipation such as pain, increased use of catheters, delirium, bowel obstruction, thereby increasing length of hospital stay. Our aim was that all our patients would have a completed stool chart. Method: Three Plan Do Study Act (PDSA) cycles were designed with input from the medical team, ward charge nurse and QIP lead. The first intervention was to discuss the importance of stool charts at board round. The second intervention included displaying a Bristol stool chart poster. The final intervention involved discussion with the clinical support workers and notices were displayed. Baseline audit data was collected and the audit repeated following each intervention. 12 patients were selected per cycle using alternate even and odd bed numbers. Data included if the amount, colour and stool type had been documented on the chart or the notes. Data was collected and presented using Google Sheets and Slides. Results: Baseline data showed 40% of patients had a completed stool chart. Following the first intervention this improved to 50%. Data collected in PDSA cycle 2 showed the worst results with 25% of charts documented. After the final intervention stool charts were completed for 42% of patients. This information was less frequently documented in the notes. Staff experience and workload were likely factors affecting documentation. Conclusion: The first intervention of active discussion with the multi-disciplinary team was most effective. Passive interventions such as displaying a poster was much less effective. There remains room for improvement and further PDSA cycles are planned.